The Role of AI in Enhancing HRM Practices A Comparative Study Across Industries - Wibowo, Eko Putro; Avian, Zakhi Bailatul Nur; Tarigan, Frandy Putra Perdamen; Erlangga, Irwan Syah; Soenanta, Andy (Penelitian dan Pengembangan Ilmu, 2024)
Application of artificial intelligence (AI) in Human Resource Management (HRM) is increasingly important in various industries to increase employee engagement and productivity. However, the impact of AI in HRM varies based on the specific characteristics of each industry, such as technology, manufacturing, services, and healthcare, demanding a targeted approach. This research aims to provide a comprehensive analysis of the role of AI in increasing employee engagement and productivity through a systematic literature review that examines research methods, industry distribution, and contextual factors that influence the effectiveness of AI in HRM. Using PRISMA methodology, a number of studies that met the inclusion and exclusion criteria were selected for analysis. The research results show that AI has a positive impact on employee engagement and productivity, but the impact varies across industries, influenced by organizational culture, skills requirements, and ethical and legal regulations. These findings provide guidance for HRM practitioners in effectively adopting AI according to the unique needs of each sector.